2022
DOI: 10.3390/plants11192536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Edaphic and Climatic Factors on Thymus pulegioides Essential Oil Composition and Potential Prevalence of Chemotypes

Abstract: Intraspecific chemical polymorphism is characteristic of essential oil bearing Thymus pulegioides (Lamiaceae). Soil chemical composition and climatic conditions can influence not only quantitative and qualitative composition of essential oils, but also on prevalence of different chemotypes in space. The purpose of study was to determine the impact of edaphic and climatic factors on T. pulegioides essential oil composition and potential chemotypes prevalence. It were investigated 131 habitats of T. pulegioides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Perhaps the different soil types occurring in different sites, could partly explain the patterns of monoterpenoid chemotype classes, as previous studies have found that e.g. soil properties influenced essential oil composition in Thymus pulegioides (Vaičiulytė et al 2017, 2022). As our study only assessed soil type at the site level, variation in soil type and relationships with individual plants within sites could not be captured, and hence small‐scale variation in soil type as driver of local chemical variation warrants future study.…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps the different soil types occurring in different sites, could partly explain the patterns of monoterpenoid chemotype classes, as previous studies have found that e.g. soil properties influenced essential oil composition in Thymus pulegioides (Vaičiulytė et al 2017, 2022). As our study only assessed soil type at the site level, variation in soil type and relationships with individual plants within sites could not be captured, and hence small‐scale variation in soil type as driver of local chemical variation warrants future study.…”
Section: Discussionmentioning
confidence: 95%
“…Total monoterpene concentration was shown to negatively influence browsing of P. sitchensis by red deer (Cervus elaphus) [35]. Genetic, edaphic, climatic, and geographic factors are often cited as affecting the essential oil profiles [36,37]. Latitudinal differences, including climatic differences, may be responsible for the lower monoterpene hydrocarbon concentrations and higher oxygenated monoterpenoid concentrations in the Oregon samples compared to the British Columbia samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, another study conducted by Robles and Garzino (2000) [30] on Cistus monspeliensis showed, conversely, that plants grown on calcareous soils presented higher oil yields than those on siliceous soils. These variations detected in essential oil yields have often been linked to the influence of specific edaphoclimatic variables [31,32] …”
Section: Resultsmentioning
confidence: 99%
“…These variations detected in essential oil yields have often been linked to the influence of specific edaphoclimatic variables. [31,32] In contrast to the strong effect observed of edaphic factors on yield, microclimatic conditions do not seem to play a consistent role in explaining variations on yield, see data shown in Table S1. Therefore, these results indicate that the EO yielded can be significantly influenced by specific edaphic variables.…”
Section: Essential Oil Yieldmentioning
confidence: 89%